Pengaruh Frugality Terhadap Niat Beli Produk Hijau dengan Motivation to Save Sebagai Variabel Mediasi - Kholifah Syafrina Hasna; Rini Kuswati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of involuntary frugality and voluntary frugality on green purchase intention with motivation to save as a mediating variable. The growing awareness of sustainable consumption highlights the importance of understanding how frugal lifestyles and saving behavior shape consumers’ intentions to purchase green products. A quantitative approach was employed using a survey of 199 respondents from Surakarta, Indonesia, who have an interest in green products. The sampling technique used was purposive sampling, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that involuntary frugality has a positive and significant effect on motivation to save but no significant effect on green purchase intention. Conversely, voluntary frugality has a positive and significant influence on both motivation to save and green purchase intention. Furthermore, motivation to save positively and significantly affects green purchase intention and mediates the relationship between voluntary frugality and green purchase intention, but not between involuntary frugality and green purchase intention. These findings reveal that voluntarily adopted frugality driven by personal awareness and sustainable values has a stronger impact on consumers’ intentions to purchase green products than frugality driven by economic constraints. The results support the Theory of Planned Behavior in explaining the role of personal values and self-control in sustainable consumer behavior.